Damage Done by Animals: Legal Qualification under Russian Law, Risk Management - Rabets, Anna P.; Kareva, Tatiana Yu. (International Review of Management and Marketing, 2016)
The article is dedicated to the issues of the legal qualification of damage done by wild and domestic animals to subjects of civil relations. Identification of the animal gathering places among the sources of increased danger is particularly relevant in connection with misregulating in the civil legislation of the Russian Federation a number of aspects related to compensation for harm caused by animals as a specific object of the civil rights to a citizen or an organization. The aim of the study was to determine the effectiveness of civil legal mechanism to protect victims injured by animals and the risk of this injury in the workplace. As follows from the definition of “risk”, it is directly associated with a specific damage. The report discusses the relationship between the concepts “harm” and “damage” from the point of view of civil law. Despite the presence of a large number of norms of the Federal Law, applying the concept of “risk”, there are two main objects of technical regulation essentially based on this concept: the definition of safety requirements and establishment of forms and schemes of mandatory conformity. Keywords: source of increased danger; animal as the object of civil rights; delict; defense of victims, insurance; risk- management JEL Classifications: D81, G32, K10